Free Cash Flow and Firms’ Growth: An Empirical Investigation of Nigerian Quoted Non - Financial Firms - Akinleye, Gideon Tayo; Olarewaju, Odunayo Magret; Fajuyagbe, Kole Samson (Journal of Economics and Behavioral Studies, 2018)
This study analyzes the effect of free cash flow on the growth of non- financial quoted firms in Nigeria. Specifically, the impact of free cash flow on the percentage change in a total asset of selected quoted firms (Dangote Flour Mills, Honeywell Nig. Plc, Dangote Sugar Refinery, Flour Mills of Nig. Plc, and PZ CussonsPlc) over a period of five years (2012 - 2016) was analysed . Data used in the study were sourced from the annual reports of the selected quoted firms. Correlation analysis, restricted F - test, Hausmantest, and some panel estimation methods (pooled OLS estimation, fixed effect estimation, and random effect estimation) were employed to analyse the data. Results revealed that free cash flow exerts a negative impact on firms ’ growth rate, to the tune of - 0.000391(p=0.179 > 0.05). The study, therefore, established that rising free cash flow has the capacity to erode the growth prospect of firms quoted on the Nigeria stock exchange. Based on this result, the study recommends that quoted firms in the country decrease their free cash flow, leverage increased turnover, explore viable/positive net present value projects, and reduce operational costs so as to be positioned for better growth in terms of percentage change in total asset.